Designing moodle-based learning media integrated with H5P interactive on chemical equilibrium topic - Hayati, Sriza; Guspatni, Guspatni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Chemical equilibrium is one of the learning materials that is difficult to understand in learning chemistry. To increase student understanding and participation in learning chemical equilibrium topics, research was conducted to design. This is because Moodle-based learning media combined with H5P on chemical equilibrium topics combines media that utilizes technology to produce an interactive learning experience. This research is included in educational design research using the Plomp development model, including the preliminary research stage by conducting need and context analysis, literature review, and theoretical framework and prototyping phase, including initial plan and self-evaluation. The research subjects were six teachers from SMAN 1 Pariaman, SMAN 2 Pariaman, and SMAN 3 Pariaman, and fifty students of SMAN 1 Pariaman. The object of this research is Moodle-based learning media integrated with H5P interactive. The instruments of this research are questionnaire sheets and interview sheets. For the results based on preliminary research data and the prototyping phase, it can be concluded that the design of Moodle-based learning media using the Plomp development model, which produces prototype II, has been successfully carried out according to the design based on the analysis results in preliminary research. I hope that the prototype in the form of Moodle-based learning integrated with H5P interactive can produce learning media that can be used in school to support chemistry learning and improve interactive learning experiences.